Numerical Development of Heat Transfer Coefficient Correlation for Spray Cooling in Continuous Casting - Ma, Haibo; Silaen, Armin; Zhou, Chenn (Frontiers in Materials, 2020)
The desire to remain competitive and continuously produce high quality and high strength steel at the maximum production rate in continuous casting requires dynamic control over the spray cooling rate. Efficient and uniform heat removal without cracking or deforming the slab during spray cooling is critical. The challenge is to obtain accurate Heat Transfer Coefficient (HTC) on the slab surface as boundary condition for solidification calculations. Experiment based HTC correlations are limited to handful operating conditions and they might fail when changes occur. The current study presents a numerical model for spray cooling featuring the simulation of atomization and droplet impingement heat transfer in continuous casting. With the aid of high-performance computer, parametric studies were performed and the results were converted into mathematically simple HTC correlations as a function of essential operating parameters. Finally, a Graphic User Interface (GUI) was developed to facilitate future applications of the correlations. The HTC prediction is stored in the versatile comma-separated values (csv) format and it can be directly applied to solidification calculations. The proposed numerical methodology should benefit the steel industry by expediting the development process of HTC correlations and can further improve the accuracy of the existing casting control systems.